A Geography Teacher's Responsiveness to the Cognitive Academic Language Proficiency (CALP) Needs of Zimbabwean English Second Language (ESL) Learners in Syllabus Interpretation and Instructional Design - Nyoni, Erick (Adonis & Abbey Publishers, 2022)
Using a document phenomenology framework, the study sought to establish a Geography teacher‘s responsiveness to the Cognitive Academic Language Proficiency (CALP) needs of Zimbabwean English Second language (ESL) learners in syllabus interpretation and instructional design. Two topics from the Geography Ordinary Level Syllabus and the subsequent six weeks‘ instructional schemes of work for 24 lessons were analysed to establish the Geography teacher‘s responsiveness to learner CALP needs. The study established that the national Geography syllabus and schemes of work were not explicit about how CALP should be developed which negatively affected formulation of instructional objectives, selection of teaching activities, and instructional media. The study recommends that teachers be retooled through in-service training to a CALP oriented framework for relevant discipline discourse patterns to be developed in learners.